Frontline Reporting from the Epicenter of a Global Pandemic: A Survey of the Impact of COVID-19 on Plastic Surgery Training in New York and New Jersey. Issue 1 (21st December 2021) - Shah, Jinesh; Zhao, Ruya; Yi, Joseph; Otterburn, David; Patel, Ashit; Szpalski, Caroline; Tanna, Neil; Taub, Peter J.; Weichman, Katie E.; Ricci, Joseph A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Since the first documented case of coronavirus disease of 2019 (COVID-19), the greater New York City area quickly became the epicenter of the global pandemic, with over 500, 000 cases and 50, 000 deaths. This unprecedented crisis affected all aspects of health care, including plastic surgery residency training. The purpose of this study was to understand the specific impact of the COVID-19 pandemic on plastic surgery residencies. Methods: A survey of all plastic surgery residency training programs in the greater New York City area was conducted. The impact to training during the peak months of infection (March and April of 2020) was evaluated using resident education as measured by case numbers, need for redeployment, and staff wellness as primary outcome variables. Results: A total of 11 programs were identified in the region, and seven programs completed the survey, with a response rate 63.6 percent. When comparing productivity in March and April of 2019 to March and April of 2020, a total decrease in surgical volume of 64.8 percent (range, 19.7 to 84.8 percent) and an average of 940 (range, 50 to 1287) cancelled clinic visits per month were observed. These decreases directly correlated with the local county's COVID-19 incidence rates (p = 0.70). A total of 83 percent of programs required redeployment to areas of need, and correlation between local incidence of COVID-19 and the percentage of residents redeployed to non–plastic surgical clinical environments by a given program (ρ = 0.97) was observed. Conclusion: As the first COVID-19 wave passes the greater New York area and spreads to the rest of the country, the authors hope their experience will shed light on the effects of the ongoing COVID-19 pandemic, and inform other programs on what to expect and how they can try and prepare for future public health crises.